Public Procurement of Energy Efficiency Services : Getting Started - World Bank (Washington, DC, 2014)
The world's primary energy needs are expected to grow rapidly over the next two decades, with the largest incremental increase coming from developing countries. This will require over US$25 trillion in energy supply infrastructure investment by 2030. Meeting the growth in energy demand through traditional energy development models is unsustainable from both environmental and energy security perspectives. Finding new ways to meet energy needs sustainably while maintaining robust socioeconomic development is imperative. This note offers more operational guidance on how to get started with such programs. It starts with a summary of the report's main findings and then delves into operational modalities of operationalizing these findings for World Bank (WB) operations, including issues of WB procurement and financing. Rather than seek to recommend changes in WB procedures, it presents some ideas and options under current WB processes to formulate operational approaches and strategies to deliver large-scale energy savings to public agencies, at both the national and local levels.